Case Report: Severe Hypernatremia From Ingestion of One's Own Urine - Kang, Waye Hann; Kamaruddin, N. A.; Sukor, Norlela (Frontiers in Medicine, 2022)
An often unrecognized cause of hypernatremia is the ingestion of fluids or substances with high osmolality. We hereby report a case of severe hypernatremia with acute kidney injury in a severely debilitated patient with acute gouty arthritis who resorted to ingesting his own urine. Hypernatremia induced by drinking urine could be attributed to many underlying mechanisms, one of the important possible causes is the resultant high serum urea that leads to significant osmotic diuresis and a further increase in free water clearance. To the best of our knowledge this is the first case report that describes this unique cause of hypernatremia.